Evaluating a Dyadic Intervention on Risk Reduction Among People Who Inject Drugs - Natalie Flath; Karin Tobin; Aleks Mihailovic; Paige Hammond; Carl Latkin (SAGE Publishing, 2018)
Among 100 people who inject drugs enrolled in a peer mentorship intervention aiming to promote injection-related risk reduction behavior change, we evaluated the role of participation in a dyad session on reducing sharing of syringes and cookers in the past 6 months. Dyad participants (n = 69) invited an injection, sex partner, or family member to the study site to reinforce learnt behavior change tools by practicing communication skills and risk reduction lessons. In all, 31 participants did not participate in the dyad session. We descriptively assessed changes in sharing injection equipment between the 2 time points of pre- and postintervention using the tests of proportions by dyad participation. Multivariable logistic regression adjusted for sex was used with an interaction term (time points × dyad participation) to evaluate the dyad effect. Dyad participants reported reduced syringe and cooker sharing at postintervention (sharing syringe: 17% versus 39%, P  < .05 and cooker: 32% versus 59%, P  < .01). There was no difference between the dyad group's sharing injection equipment behavior after the intervention (sharing syringes: adjusted odds ratio [aOR] 0.76; 95% confidence interval [CI] 0.1-3.9 and cookers: aOR 0.72; 95% CI 0.1-3.5). The role of the dyad session alone on risk taking was not effective. With a small sample size, it is important to continue to evaluate the nature of peer-based dyadic experiences in future studies.